Xenograft of microencapsulated Sertoli cells restores glucose homeostasis in db/db mice with spontaneous diabetes mellitus. (27th September 2016) - Luca, Giovanni; Arato, Iva; Mancuso, Francesca; Calvitti, Mario; Falabella, Giulia; Murdolo, Giuseppe; Basta, Giuseppe; Cameron, Don F.; Hansen, Barbara C.; Fallarino, Francesca; Baroni, Tiziano; Aglietti, Maria Chiara; et al.
Abstract: Background: Increased abdominal fat and chronic inflammation in the expanded adipose tissue of obesity contribute to the development of insulin resistance and type 2 diabetes mellitus (T2D). The emerging immunoregulatory and anti‐inflammatory properties of Sertoli cells have prompted their application to experimental models of autoimmune/inflammatory disorders, including diabetes. The main goal of this work was to verify whether transplantation of microencapsulated prepubertal porcine Sertoli cells (MC‐SC) in the subcutaneous abdominal fat depot of spontaneously diabetic and obese db/db mice (homozygous for the diabetes spontaneous mutation [Lepr db ]) would: (i) improve glucose homeostasis and (ii) modulate local and systemic immune response and adipokines profiles. Methods: Porcine prepubertal Sertoli cells were isolated, according to previously established methods and enveloped in Barium alginate microcapsules by a mono air‐jet device. MC‐SC were then injected in the subcutaneous abdominal fat depot of db/db mice. Results: We have preliminarily shown that graft of MC‐SC restored glucose homeostasis, with normalization of glycated hemoglobin values with improvement of the intraperitoneal glucose tolerance test in 60% of the treated animals. These results were associated with consistent increase, in the adipose tissue, of uncoupling protein 1 expression, regulatory B cells, anti‐inflammatory macrophages and a concomitant decrease of proinflammatory macrophages. Furthermore, the treated animals showed a reduction in inducible NOS and proinflammatory molecules and a significant increase in an anti‐inflammatory cytokine such as IL‐10 along with concomitant rise of circulating adiponectin levels. The anti‐hyperglycemic graft effects also emerged from an increased expression of GLUT‐4, in conjunction with downregulation of GLUT‐2, in skeletal muscle and liver, respectively. Conclusions: Preliminarily, xenograft of MC‐SC holds promises for an effective cell therapy approach for treatment of experimental T2D.